Bedsitters - Zwartjes, Frans (The Netherlands, 1973)
Set on the landing and the stairs of Zwartjes’ new house, then still empty, in The Hague. The filmmaker suggests a mysterious and complex space by using a ‘floating’ camera to film a number of crawling, creeping personages.
Silent
Verzio Film Festival Submission
Keywords: Experimental films